2014
DOI: 10.5388/aon.2014.14.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climacteric Symptoms and Fatigue on the Quality of Life in Breast Cancer Survivors: The Mediating Effect of Cognitive Dysfunction

Abstract: The instruments used in this study were climacteric symptoms, fatigue, cognitive dysfunction, and the QOL scales. Data were analyzed using descriptive statistics, correlation, and pathway. Results: Cognitive dysfunction was directly affected by climacteric symptoms and fatigue. QOL was directly affected by fatigue, However climacteric symptoms and cognitive dysfunction did not effect on QOL directly. Impact of climacteric symptoms on QOL, mediating effect of cognitive dysfunction was not confirmed. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Likewise, a study of breast cancer survivors with completed surgeries and assistive treatments, breast cancer survivors whose treatment had ended had scores of 53.4 and 56.66 points, respectively for breast cancer survivors with completed surgeries and assistive treatments [25,26]. On the other hand, a report of 110 adult females with breast cancer or OB/GYN cancers [33] indicated that quality of life according to cancer survival stage was 58.7, 62.3, and 66.8 points during the acute, extended, and permanent stages, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a study of breast cancer survivors with completed surgeries and assistive treatments, breast cancer survivors whose treatment had ended had scores of 53.4 and 56.66 points, respectively for breast cancer survivors with completed surgeries and assistive treatments [25,26]. On the other hand, a report of 110 adult females with breast cancer or OB/GYN cancers [33] indicated that quality of life according to cancer survival stage was 58.7, 62.3, and 66.8 points during the acute, extended, and permanent stages, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With the number of cancer survivors steadily increasing, there has been an increase in the number of studies published on cancer survivors internationally [22,24]. In Korea in particular, there have been studies on recurrence-prevention behaviors and quality of life [25], the factors influencing quality of life [10], fatigue and quality of life [26], distress and quality of life [27], and symptoms and quality of life among breast cancer survivors [8]. Most of these studies focused on breast cancer survivors, but few studies focus on overall quality of life and the related influential factors.…”
Section: Introductionmentioning
confidence: 99%